Recovery from ketamine-induced amnesia by blockade of GABA-A receptor in the medial prefrontal cortex of mice. (6th March 2017) - Farahmandfar, Maryam; Akbarabadi, Ardeshir; Bakhtazad, Atefeh; Zarrindast, Mohammad-Reza
Highlights: Pre-training systemic administration of ketamine decreased memory acquisition. Pre-training intra-mPFC injection of muscimol, and baclofen, impaired memory acquisition. Co-pretreatment of muscimol and baclofen with ketamine, caused inhibition of memory formation. Intra-mPFC administration of bicuculline and phaclofen did not affect memory acquisition. Amnesia induced by pre-training ketamine, decreased by pretreatment of bicuculline. Abstract: Ketamine and other noncompetitive N-methyl-d -aspartate (NMDA) receptor antagonists are known to induce deficits in learning and cognitive performance sensitive to prefrontal cortex (PFC) functions. The interaction of a glutamatergic and GABAergic systems is essential for many cognitive behaviors. In order to understand the effect of γ-aminobutyric acid (GABA)/glutamate interactions on learning and memory, we investigated the effects of intra medial prefrontal cortex (mPFC) injections of GABAergic agents on ketamine-induced amnesia using a one-trial passive avoidance task in mice. Pre-training systemic administration of ketamine (5, 10 and 15 mg/kg, i.p.) dose-dependently decreased the memory acquisition of a one-trial passive avoidance task. Pre-training intra-mPFC injection of muscimol, GABAA receptor agonist (0.05, 0.1 and 0.2 μg/mouse) and baclofen GABAB receptor agonist (0.05, 0.1, 0.5 and 1 μg/mouse), impaired memory acquisition. However, co-pretreatment of different doses of muscimol and baclofen with a lower dose of ketamine (5 mg/kg), which did not induce amnesia by itself, caused inhibition of memory formation. Our data showed that sole pre-training administration of bicuculline, GABA-A receptor antagonist and phaclofen GABA-B receptor antagonist into the mPFC, did not affect memory acquisition. In addition, the amnesia induced by pre-training ketamine (15 mg/kg) was significantly decreased by the pretreatment of bicuculline (0.005, 0.1 and 0.5 μg/mouse). It can be concluded that GABAergic system of the mPFC is involved in the ketamine-induced impairment of memory acquisition.